Municipal Solid Waste to Energy Generation in Bangladesh: Possible Scenarios to Generate Renewable Electricity in Dhaka and Chittagong City - Islam, K. M. Nazmul (Journal of Renewable Energy, 2016)
Increased generation of methane (CH4) from municipal solid wastes (MSW) alarms the world to take proper initiative for the sustainable management of MSW, because it is 34 times stronger than carbon dioxide (CO2). Mounting land scarcity issue around the world brands the waste to energy (WtE) strategy for MSW management in urban areas as a promising option, because WtE not only reduces the land pressure problem, but also generates electricity, heat, and green jobs. The goal of this study is to evaluate the renewable electricity generation potential and associated carbon reduction of MSW management in Bangladesh using WtE strategies. The study is conducted in two major cities of Bangladesh: Dhaka and Chittagong. Six different WtE scenarios are evaluated consisting of mixed MSW incineration and landfill gas (LFG) recovery system. Energy potential of different WtE strategy is assessed using standard energy conversion model and subsequent GHGs emissions models. Scenario A1 results in highest economic and energy potential and net negative GHGs emission. Sensitivity analysis by varying MSW moisture content reveals higher energy potential and less GHGs emissions from MSW possessing low moisture content. The study proposes mixed MSW incineration that could be a potential WtE strategy for renewable electricity generation in Bangladesh.